(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2020)
Since 2006, the education of imprisoned people was added as a modality of the formal education system under the regulation of the National Education Law 26.206. In light of these new circumstances, theoretical frameworks were needed in order to understand deeply the different issues in these spaces.This paper has the purpose of analyze how the peculiarities of confinement contexts allow understanding the difficulties that students show when studying history. The institutionalized educational practices developed in the high level education Center 460 will be taken as a point of departure. This school institution, which started its activities in 2011, is located in the Greater Buenos Aires penitentiary complex and depends on the government of the province of Buenos Aires. Although this educational space is a unique and particular case, its analysis allows the identification of general keys, signs and symptoms related to the functioning of educational institutions in the context of confinement in general.